Enzyme-catalysed regio- and enantioselective preparative scale synthesis of (S)-2-hydroxy alkanones1. Issue 48 (28th May 2015) - Loderer, C.; Ansorge-Schumacher, M. B.
<x xml:space="preserve">Abstract</x> The alcohol dehydrogenase CPCR2 was applied for the asymmetric reduction of 2, 3-alkanediones to the corresponding (S)-2-hydroxy alkanones with high regio- and stereoselectivity and in preparative scale.